2018
DOI: 10.1097/dcr.0000000000001226
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Epidural Analgesia: Does It Enhance Recovery?

Abstract: BACKGROUND: Thoracic epidural analgesia has been shown to be an effective method of pain control. The utility of epidural analgesia as part of an enhanced recovery after surgery protocol is debatable. OBJECTIVE: This study aimed to determine if the use of thoracic epidural analgesia in an enhanced recovery after surgery protocol decreases hospital length of stay or inpatient opioid consumption after elective colorectal resection. DESIGN: Single institution retrospective cohort study. SETTINGS: The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In the study by Rosen et al (2018) 15 showed that, in the context of multimodal analgesia following the ERAS protocol, the use of epidural anesthesia had no impact on the length of stay or consumption of opioids in-hospital after colorectal surgeries, as we noted in our study that the patients in both groups had the same hospital discharge time due to their aptitude for this, with average pain without significant differences, as well as the presence of a return of gastrointestinal motility, confirming the finding of the Cochrane systematic review (2016) 12 in which there was very low quality evidence, showing that an epidural anesthesia containing a local anesthetic could reduce the hospital stay for open surgery.…”
Section: Discussionmentioning
confidence: 97%
“…In the study by Rosen et al (2018) 15 showed that, in the context of multimodal analgesia following the ERAS protocol, the use of epidural anesthesia had no impact on the length of stay or consumption of opioids in-hospital after colorectal surgeries, as we noted in our study that the patients in both groups had the same hospital discharge time due to their aptitude for this, with average pain without significant differences, as well as the presence of a return of gastrointestinal motility, confirming the finding of the Cochrane systematic review (2016) 12 in which there was very low quality evidence, showing that an epidural anesthesia containing a local anesthetic could reduce the hospital stay for open surgery.…”
Section: Discussionmentioning
confidence: 97%
“…However, the effectiveness of epidurals has to be investigated regarding MIS and fast track. A reduced length of stay was demonstrated for open surgery only but not for MIS [31]; furthermore, there is single-center acquired data suggesting no significant effect of epidurals on opioid consumption and length of stay after colorectal surgery regardless of the surgical technique which leads these authors to exclude epidural anesthesia from their fast-track protocols [62]. Considering the technical challenge of placing a thoracic epidural catheter and its side effects like urinary retention which might hinder patients' mobilization, there is emerging use of alternative procedures.…”
Section: Epidural Cathetermentioning
confidence: 99%
“…On the contrary, several studies which evaluated incorporating TEA as a component on MMA for laparoscopic colorectal surgeries and thoracic surgeries did not find any additional benefit of TEA. [15][16][17] In a dose ranging from 200-300 ÎŒg, a single dose of intrathecal morphine (ITM) has been found superior to MMA including systemic opioids in patients undergoing colonic surgeries, hepato-pancreatic-biliary Category of surgery Various regional anaesthesia techniques 33] Studies have demonstrated that a continuous TAP infusion is non-inferior to continuous TEA in patients undergoing colorectal surgeries. Single-shot TAP block was found to provide improved postoperative analgesia after LSCS which was although lesser compared to ITM, but had lesser side effects when compared to ITM.…”
Section: Available Evidence Regarding Implementation Of Ra In Erasmentioning
confidence: 99%